Inhibitory Effects of Carbazomycin B Produced by Streptomyces roseoverticillatus 63 Against Xanthomonas oryzae pv. oryzae - Shi, Tingting; Guo, Xin; Zhu, Jiali; Hu, Lingming; He, Zhipeng; Jiang, Donghua (Frontiers in Microbiology, 2021)
The present manuscript highlights the potential role of Streptomyces roseoverticillatus 63 (Sr-63) against Xanthomonas oryzae pv. oryzae (Xoo), which is the cause of a disastrous bacterial leaf blight disease with rice worldwide. The disease suppression was achieved under greenhouse conditions. A foliar spray of the fermentation broth of Sr-63 significantly reduced the leaf blight symptoms with rice in Xoo inoculated rice plants. Furthermore, we observed that the carbazomycin B, isolated from the fermentation broth of Sr-63, was demonstrated to have antibacterial activity against Xoo with a minimum inhibitory concentration (MIC) of 8 μg mL–1. The results indicated that carbzomycin B hampered the membrane formation of Xoo, reduced the production of xanthomonadin and extracellular polymeric substance (EPS). The fourier transform infrared spectroscopic (FT-IR) indicated that carbazomycin B changed the components of the cell membrane, then caused a change of the cell surface hydrophobicity of Xoo. Scanning electron microscopy revealed that the Xoo cells treated with carbazomycin B exhibited apparent structural deformation. The results also indicated that carbazomycin B had a negative impact on the metabolism of Xoo, carbazomycin B reduced the activity of malate dehydrogenase (MDH) activity and suppressed the protein expression of Xoo. Overall, our data suggests that Streptomyces roseoverticillatus 63 is a promising biocontrol agent that could be used to combat the bacterial leaf blight diseases of rice.